“Everything Is Old”: National Socialism and the Weathering of the Jews of Łódź - Elizabeth Strauss (Genealogy, 2024)
Using the social scientific theory of “weathering”, the case study presented here reveals the broader explanatory power of the theory. Arline Geronimus developed the concept to describe the impact of racist systems on marginalized populations. Based on more than four decades of empirical research, Geronimus posits that the cumulative impact of navigating the structural racism embedded in US institutions results in accelerated declines in health and premature aging. The historical case study of the Łódź ghetto demonstrates that Nazi persecution of the Jews during the Holocaust resulted in a similar process of weathering among Jews. From 1939 to 1945, German authorities systematically dispossessed and uprooted, purposely starved, and exploited for labor the tens of thousands of Jews held captive in the Łódź ghetto. Despite valiant Jewish efforts to ameliorate the hardships of life in the ghetto, the persistent onslaught of racist policies and degradation ultimately resulted in widespread weathering of the population on an individual and communal level. I propose that the concept of “weathering” developed by social scientists has broad interpretative power for understanding the personal and communal impact of white supremacist societies in a historical context. The case of the Łódź ghetto is instructive beyond what it reveals about the particular persecution of the Jews during the Third Reich. The abrupt imposition of a racist system of government, the steady escalation of antisemitic policies from oppression and exploitation to genocide, and the relatively short duration of the ghetto’s existence lays bare the cumulative effects of widespread individual weathering on the vitality of the community itself. In the Łódź ghetto, prolonged exposure to an environment governed by white supremacy also resulted in communal weathering.